2017
DOI: 10.1093/jamia/ocx020
|View full text |Cite
|
Sign up to set email alerts
|

Patient portals and broadband internet inequality

Abstract: The majority of adults with outpatient visits to a large urban health care system did not use the patient portal, and initiation of use was lower for racial and ethnic minorities, persons of lower socioeconomic status, and those without neighborhood broadband internet access. These results suggest the emergence of a digital divide in patient portal use. Given the scale of investment in patient portals and other internet-dependent health information technologies, efforts are urgently needed to address this grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(139 citation statements)
references
References 35 publications
7
131
1
Order By: Relevance
“…Among this VA cohort who took active steps to enroll in, and gain access to, patient portal functions, short-term and long-term portal usage were significantly associated with having broadband Internet at home, high self-rated ability to use the Internet, and overall online behavior. Access to broadband Internet has emerged as a social determinant of health [ 27 ], defined as, “a condition in which people are born, grow, live, work, and age, and which shapes their health status” [ 28 ]. As virtual health care becomes more commonplace, affordable broadband Internet and devices, and digital know-how, will be needed to ensure equity in care services [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among this VA cohort who took active steps to enroll in, and gain access to, patient portal functions, short-term and long-term portal usage were significantly associated with having broadband Internet at home, high self-rated ability to use the Internet, and overall online behavior. Access to broadband Internet has emerged as a social determinant of health [ 27 ], defined as, “a condition in which people are born, grow, live, work, and age, and which shapes their health status” [ 28 ]. As virtual health care becomes more commonplace, affordable broadband Internet and devices, and digital know-how, will be needed to ensure equity in care services [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are unable to afford, access, or use these technologies will be unable to benefit from this technology. There is strong evidence that certain populations already experience this digital divide-for example, patients with low health literacy are less likely to use health information technology, 49 minorities and patients of lower socioeconomic status are less likely to use patient portals, 50 and users of mobile technology specifically are more likely to be younger, higher educated, male, and reside in zip codes with higher median income, 51,52 though there is evidence that smartphone ownership is increasing in low-income and low-education populations. 53 Further work is needed to understand how to close this divide further so that all populations are able to benefit from new digital health tools.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, Ancker et al found that the odds of being given an access code for a patient portal were higher for patients who were young, English speakers, white, insured, and female [ 6 ]. Patients with lower socioeconomic status were less likely to make use of patient portals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%